Application-Based Instructional Tools for Enhancing Students' Problem Solving Skills in Home Economics - Nurlaela, Luthfiyah -; Romadhoni, Ita Fatchur; Widodo, Wahono -; A, Ana - (Journal of Technical Education and Training, 2017)
The main purpose of education is to help students learn in a way that allows them to use what they have learned in solving problems in new situations. As problem solving acts as the basis of education, lecturers are expected to develop students' ability on it. This study aims to describe (1) the working course plan in inducing problem solving skills in various learning models, (2) student's activity during the learning process, and (3) the problem solving skills after the class ends. This study implemented instructional tools to boost students' problem solving skills, of which was conducted at Home-Economics Department, Universitas Negeri Surabaya (UNESA) with 67 participants. The instruments included a work- sheet of the developed course plan, observation sheet of learning activities, and test. Data were analyzed using descriptive qualitative and quantitative analysis methods. Results showed that the students improved their higher order thinking skills into more critical and creative during the learning activities. In conclusion, the use of appliances in home economics instructional tools can increase students' problem solving skills because the agreement of the interconnected systems or subsystems with the problems faced.